Pelaksanan Pembelajaran Bahasa Indonesia Masa Pandemi Covid-19 di SMA Negeri 11 Pekanbaru - Herawati, Delvina; Supriyadi (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
Learning in the Covid-19 Pandemic Period at SMA Negeri 11 Pekanbaru. Undergraduate Program. Riau Islamic University. This research is entitled "Implementation of Indonesian language learning during the covid-19 pandemic at SMA Negeri 11 Pekanbaru". Implementation of learning is one of the steps that must be taken by teachers and students. Based on the observations that the authors got in the field in the preliminary activities the teacher did not carry out the implementation of learning in explaining the learning objectives or basic competencies to be achieved, in the core activities the teacher rarely carried out exploration, elaboration and confirmation activities. The problem in this research is how to implement Indonesian language learning during the covid-19 pandemic at SMA Negeri 11 Pekanbaru. This study aims to find out how the implementation of learning during the covid-19 pandemic at SMA Negeri 11 Pekanbaru seen from preliminary activities, core activities and closing activities. The theory used in this study is Kunandar (2011). The method in this study is a qualitative case study method. The techniques used in this research are questionnaires, observations, interviews and documentation studies. The results showed that based on case studies, it was found that learning implementation activities were ineffective and students were less active in learning based on the results of filling out questionnaires and connecting with online learning lesson plans, it can be seen in its implementation that not all activities were carried out by teachers starting from preliminary activities, core activities, activities closing.